PENGEMBANGAN MODEL DIKLAT GURU SOSIOLOGI SMA TENTANG PEMBELAJARAN INKUIRI BERBASIS BUDAYA LOKAL - Gunarso Gunarso; Bambang Suteng Sulasmono (Kelola: Jurnal Manajemen Pendidikan, 2015)
This development study is aimed to develop a model of training for sociology teacher using inquiry based on local culture. It is done through some steps which are recognizing the potential and problems, formulating a design, composing and performing device validation. Based on the research has resulted a module of training for inquiry learning based on local culture validated and revised by experts. The module is ready to use for training to improve teachers’ competence. The plannings done before training are determining training needs through analyzing the needs of the organization deciding a training program,composing an initial assessment and end of the craft success criteria for training.The implementation of training development about inquiry based on local culture for sociology teachers is emphasized in making lesson plan containing characters value in Sociology. Monitoring and evaluation for quality assessment done by filling out the questionnaire by the trainees so that they are able to know the response to the committee and speakers. While the evaluation of trainees can be done through tests and assignment of making learning about inkuiri RPP based on local culture.